INCIDENCE OF BRONCHOPULMONARY DYSPLASIA IN PRETERM NEWBORNS SUBMITTED TO MECHANICAL VENTILATION: A RETROSPECTIVE STUDY OF 1250 PRETERM NEWBORNS - Vieira, Leilianna de Souza; de Vasconcelos, Thiago Brasileiro; de Freitas, Nilce Almino; de Sousa, Cristiano Teles; Magalhães, Clarissa Bentes de Araujo; Câmara, Teresa Maria da Silva; Barros, Geórgia Guimarães; Bastos, Vasco Pinheiro Diógenes (Journal of Health & Biological Sciences, 2014)
Objective: To determine the incidence of preterm newborn infants in mechanical ventilation who developed bronchopulmonary dysplasia in a public hospital at Fortaleza/CE. Method: Descriptive, retrospective and longitudinal quantitative analysis with 1250 preterm infants admitted to the Intensive Care Unit, Dr. César Cals General Hospital, at Fortaleza, from July 2006 to June 2007. Data collection occurred during two months, with visits to units twice a week, where the medical records were done. Were included in these sample newborns that were in mechanical ventilation and developed bronchopulmonary dysplasia. Then the gestational average was 28.6 weeks; the mean weight of infants was 1125.33 grams, born vaginally or cesarean section, of both sexes and with various primary diseases such as respiratory distress syndrome, jaundice and neonatal infection. Results: In the sample from the total admissions, 34.48% were for mechanical ventilation and 3.48% developed bronchopulmonary dysplasia. Conclusion: Despite the low prevalence, bronchopulmonary dysplasia is a important complication of prematurity, directly related to the duration of mechanical ventilation, thus the team must be committed on weaning and extubation of those as soon as possible, preferably within the first week of life.